Effect of Infection by Metarhizium anisopliae (Hypocreales: Clavicipitaceae) on the feeding and oviposition of the pea leafminer Liriomyza huidobrensis (Diptera: Agromyzidae) on different host plants - Migiro, Lorna Nyangarisa; Maniania, N.K.; Chabi-Olaye, A.; Wanjoya, A.; Van den Berg, Johann (Elsevier Science, 2011)
The effect of fungal infection by Metarhizium anisopliae on feeding and oviposition of adult Liriomyza huidobrensis was examined on three host plants, faba bean (Vicia faba), French bean (Phaseolus vuklgaris) and snow pea (Pisum sativum) in the laboratory. Flies were contaminated with dry conidia and allowed to feed and oviposit on the different host plants. Mortality in L. huidobrensis varied between 14% and 20% in the controls and between 77% and 100% in fungal treatments 120 h post-infection for the three host plants. L. huidobrensis made more punctures (47.3-52.6 cm-2) in the control than in the fungal treatments (23.1-26.9 cm-2) for the three host plants. The cumulative average number of punctures cm-2/female by L. huidobrensis was higher in the controls than in fungal treatments from 72 h post-treatment in faba bean (12.2 vs. 8.2) and French bean (14.8 vs. 8.9), and from 48 h post-inoculation in snow pea (8.5 vs. 5.7). Female L. huidobrensis laid more eggs in the control (0.6-6.1) than in fungal treatments (0.2-1.5) across the host plants tested. The cumulative mean number of eggs cm-2/female was significantly higher in the controls than in fungal treatments from 48 h post-treatment in faba bean (0.4 vs. 0.2) and French bean (0.1 vs. 0), and 96 h post-inoculation in snow pea (0.2 vs. 0.1). The host plant did not affect the average total number of punctures but had a significant effect on egg laying, with faba bean harboring greater number of eggs in both control and fungal treatments. A proper timeline application of the fungus before onset of feeding and oviposition peaks will be crucial in field suppression of the pest using M. anisopliae. In addition, a great consideration must be given to the target host plants prior to application of the fungus.
Keywords: Liriomyza leafmine; Liriomyza huidobrensis; feeding; oviposition; host plant; Metarhizium anisopliae